Effects of Eurycoma longifolia jack (Tongkat Ali) alcoholic root extract against oral pathogens - Alloha, Irani; Aziz, Nurul Ain Liyana; Faisal, Ghasak Ghazi; Arzmi, Mohd Hafiz; Abllah, Zurainie (2018)
Introduction: Eurycoma longifolia jack (E.L) is a herbal medicinal plant of South-East Asian origin, popularly recognized as ‘Tongkat Ali.’ The plant roots have been scientifically proven to have many biological effects including antibacterial activity however, no previous research to date has studied the effect on oral pathogens including cariogenic bacteria.This study was done to determine the antibacterial and antifungal activities of E.L. root extract against three common oral pathogens. Material and Methods: The microorganisms used were Candida albicans, Streptococcus mutans and Lactobacillus casei.: E.L root was extracted using soxhlet method. Disc diffusion assay was conducted using extract concentration of 200mg/ml. Nystatin and Ampicillin were used as positive control for fungal and bacterial tests respectively. Minimum Inhibitory Concentration (MIC) was done to determine the lowest inhibitory concentration of the extract on the microorganisms. Results: E.L extract inhibited the growth of Candida albicans and Streptococcus mutans at a concentration of 200mg/ml with a zone of inhibition of 16.0 ± 3.0mm and 7.0 ± 1.0mm respectively. There was no antimicrobial effect of the extract on Lactobacillus casei. The MIC of E.L extract against both Candida albicans and Streptococcus mutans was 25mg/ml. Conclusions: The results from this study revealed the potential use of Eurycoma longifolia jack as an antimicrobial agent which can be used to produce new oral care products.